Transcriptome and proteome of ovarian tissues revealed the differences in the ovaries of dairy goats during the breeding and non-breeding seasons - Shi, Chenbo; Liu, Qingqing; Wang, Wei; He, Qiuya; Zhao, Jianqing; Zhang, Fuhong; Zhu, Lu; Luo, Jun (Frontiers in Veterinary Science, 2025)
Dairy goats represent a crucial species within global dairy livestock. In temperate regions with distinct seasons, dairy goats exhibit reduced reproductive activity under long photoperiod conditions—a phase termed the non-breeding season. This poses a significant challenge to sustaining year-round goat milk production. As the pivotal organ for reproduction, the molecular regulatory mechanisms of the ovary in seasonal breeding remain incompletely characterized. This study investigated the variations in gonadotropin levels in dairy goats across breeding and non-breeding seasons, alongside an evaluation of follicle size and quantity. Furthermore, ovarian differences were explored at the molecular level using transcriptomic and proteomic methodologies. The findings indicate that follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels in dairy goats are significantly reduced during the non-breeding season compared to the breeding season (p < 0.05). Furthermore, follicle sizes in dairy goats are notably larger during the breeding season relative to the non-breeding season (p < 0.05). A total of 1,115 differentially expressed genes (DEGs) were identified, comprising 749 upregulated and 366 downregulated genes. Additionally, 520 differentially expressed proteins (DEPs) were identified, with 162 upregulated and 358 downregulated. The identified common DEGs and DEPs exhibiting consistent expression patterns include TMEM205, TM7SF2, SLC35G1, GSTM1, and ABHD6. These DEGs and DEPs suppress follicular development during the non-breeding season by regulating steroid hormone biosynthesis. In conclusion, this study reveals the molecular basis underlying seasonal reproductive differences at the ovarian level in dairy goats, offering new insights into the mechanisms of their seasonal reproduction.